(untitled) (Nigerian Journal of Technology, 2015)
This research work investigates the power output obtained from ethanol- diesel mix from a diesel engine. A 1% to 5% by volume of 99.6% ethanol was mixed with diesel fuel. A 500ml of each mix was used to power a 9.545kW diesel engine and the engine speed, torque, power and specific fuel consumption (sfc) were determined. Performance test indicates a 4.2% drop in power output at a 5% ethanol addition to diesel and an increase in specific fuel consumption by 1.2%. Five volumetric dilution were made resulting in the following trend: flash point ( , kinematic viscosity (4.212 , 3.773mm2/s, 3.533 mm2/s, 3.207 mm2/s, 3.016 mm2/s, 2.965 mm2/s ); dynamic viscosity (3.5 MPa.s, 3.1 MPa.s, 2.9 MPa,s, 2.6 MPa.s, 2.4 MPa.s, 2.3 MPa.s) and density ( 0.8310, 0.82158, 0.8208, 0.8108, 0.7958, 0.7758); Shaft speed (1423rpm, 1352rpm, 1286rpm, 1193rpm, 1135rpm, 1052rpm); torque (64Nm ,67Nm ,70Nm, 75Nm , 78Nm, 83Nm); Power output (9.545kW, 9.487kW, 9.428kW, 9.371kW, 9.272kW, 9.142kW) with increased ethanol addition. This shows that the energy content of ethanol-diesel mix is lower than that of diesel fuel leading to a low power output compared to diesel fuel. http://dx.doi.org/10.4314/njt.v35i1.13